Strategic planning of forest recreation and nature tourisme - Bell, Simon (2009)
In an increasingly urbanized world more and more people are turning to our forests and woodland for recreation and tourism. Planning and providing for this growing demand poses challenges that need to be addressed by managers and designers alike. Based on a study of forest recreation from across Europe, the editors bring together the expertise of more than eighty leading professionals and academics to provide a clear and concise guide to best practice. Case studies and careful research give a detailed insight into the issues that forest recreation raises, from strategic planning to integration into the existing rural economy. This chapter, being the first in Part Ill, is intended to demonstrate how the materials presented primarily in Part II can be applied to the strategic aspects of recreation and nature tourism planning in Europe. As well as the aspects brought from Part II, other requirements and issues will also be covered such as the likely effect of different drivers of leisure and recreation that are currently affecting society across Europe and are likely to set the scene for the next couple of decades, as discussed in Chapter I. Likewise, the ways that people participate in forest recreation and nature tourism vary from one European region to another, based on a number of factors which together can be called 'forest culture'. Given the benefits and values of recreation identified and demonstrated in Chapter 2 in Part I, it is also worth examining how strateg1c planning can use the evidence of these in order to target supply of recreation where there is likely to be most benefit to society.